Resistance to corporate agri-food. The case of plant-based meat - Alessandro Bonanno (Estudos de Sociologia)
Resistance to corporate domination is one of the characteristics of agri-food in the era of global neoliberalism. In the case of meat, this resistance targets not only production systems – such as CAFOs – but also, and above all, the consumption of industrially produced meat and meat products. This article probes the research question of the extent to which the development of plant-based meat is an effective alternative to corporate industrial meat production. Through the analysis of two plant-based meat companies, Beyond Meat and Impossible Foods, this work illustrates the limits of the market based business model adopted by these companies. It allows established transnational corporations to appropriate spaces of resistance historically occupied by left leaning groups and discourses. Among the major new initiatives in the global financial market and in the mass consumption sector (fast food and restaurant chains), plant-based meat is a proposal that has received widespread support from all sides of the political spectrum. The article offers a critique of the assumed “progressive” ideology and practices associated with plant-based meat and concludes with a critique of the limits of a technically based proposal.